2023
DOI: 10.1021/acsabm.3c00682
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polysulfobetaine Inhibits Cancer Cell Migration Owing to Actin Cytoskeleton Dynamics

Shubham Das,
Arnab Banerjee,
Subhadip Roy
et al.

Abstract: Cell migration is an essential dynamic process for most living cells, mainly driven by the reorganization of actin cytoskeleton. To control actin dynamics, a molecular architecture that can serve as a nucleator has been designed by polymerizing sulfobetaine methacrylate. The synthesized zwitterionic polymer, poly(sulfobetaine methacrylate) (PZI), effectively nucleates the polymerization process of G-actin and substantially accelerates the rate of polymerization. Isothermal titration calorimetry (ITC) and bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We have shown that monomeric HCP engages with actin monomers through various residues, predominantly featuring positively charged residues (Figure B). Prior research has demonstrated that actin, being negatively charged, preferentially interacts with positively charged surfaces . However, our depiction does not fully capture the likely scenario in solution, where the HCP hexamer can sequester multiple actin monomers simultaneously, which needs to be checked in the future.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We have shown that monomeric HCP engages with actin monomers through various residues, predominantly featuring positively charged residues (Figure B). Prior research has demonstrated that actin, being negatively charged, preferentially interacts with positively charged surfaces . However, our depiction does not fully capture the likely scenario in solution, where the HCP hexamer can sequester multiple actin monomers simultaneously, which needs to be checked in the future.…”
Section: Resultsmentioning
confidence: 92%
“…Actin polymerization assay was performed following a previously published protocol with slight modifications . 12 μM G-actin mix (10% pyrene-labeled actin and 90% unlabeled actin) was prepared in G-buffer (10 mM Tris pH 7.5, 0.2 mM ATP, 0.2 mM DTT, and 0.2 mM CaCl 2 ).…”
Section: Methodsmentioning
confidence: 99%